Japanese guidelines for peroral endoscopic myotomy: 1st edition. Issue 1 (14th November 2018) - Isomoto, Hajime; Ikebuchi, Yuichiro
Abstract : This Editorial refers to the article by H. Inoue, p 563‐579 of the issue DEN 30:5.